Photographs of William Blandowski (as filmed by the AJCP) [M853] - Blandowski, William, 1822-1878; Australian Joint Copying Project; National Library of Australia; State Library of New South Wales (Canberra : Australian Joint Copying Project, 1950)
Album of 142 photographs of engravings, mostly of Aborigines, entitled Australien in 142 photographischen.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the State Library of New South Wales.
National Library of Australia holds microfilm master.
Australian Joint Copying Project handbook. Part 8 : Miscellaneous [M series]
Australian Joint Copying Project miscellaneous series M853.
Also available online
Microfilm copy of originals held by Haddon Library, Museum of Archaelology and Ethnology, Cambridge, England.
Keywords: Aboriginal Australians -- Portraits